2004
DOI: 10.1074/jbc.m311894200
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self-assembling Nuclear Targeting Vector System Based on the Tetracycline Repressor Protein

Abstract: The ultimate destination for most gene therapy vectors is the nucleus and nuclear import of potentially therapeutic DNA is one of the major barriers for nonviral vectors. We have developed a novel approach of attaching a nuclear localization sequence (NLS) peptide to DNA in a non-essential position, by generating a fusion between the tetracycline repressor protein TetR and the SV40-derived NLS peptide. The high affinity and specificity of TetR for the short DNA sequence tetO was used in these studies to bind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…This SV40 sequence, termed a DNA targeting sequence (DTS), has been shown to be active in cell lines derived from monkey, rat, mouse, hamster, chicken, and human origin . Other sequences having similar ability to promote plasmid nuclear import have also been identified (see below) [Langle-Rouault et al 1998;Vacik et al 1999;Zennou et al 2000;Mesika et al 2001;Vaysse et al 2004;Mesika et al 2005;Arhel et al 2006]. However, it should be stressed that such sequence-specific nuclear import appears to be important mainly in the absence of cell division.…”
Section: Sequence-specific Nuclear Import Of Plasmid Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…This SV40 sequence, termed a DNA targeting sequence (DTS), has been shown to be active in cell lines derived from monkey, rat, mouse, hamster, chicken, and human origin . Other sequences having similar ability to promote plasmid nuclear import have also been identified (see below) [Langle-Rouault et al 1998;Vacik et al 1999;Zennou et al 2000;Mesika et al 2001;Vaysse et al 2004;Mesika et al 2005;Arhel et al 2006]. However, it should be stressed that such sequence-specific nuclear import appears to be important mainly in the absence of cell division.…”
Section: Sequence-specific Nuclear Import Of Plasmid Dnamentioning
confidence: 99%
“…When EBV nuclear antigen (EBNA)-1 expressing cells were cytoplasmically microinjected with plasmids containing the oriP DTS, increased gene expression was detected when compared to plasmids lacking oriP [Langle-Rouault et al 1998]. More recently, combinations of the tet operator and a modified tetracycline repressor containing an NLS (tetO and TetR-NLS, respectively) have been used in cis and trans to show that nuclear import can be controlled and enhanced by protein-DNA interactions [Vaysse et al 2004;Vaysse et al 2006]. When multiple copies of the tetO sequence were cloned into a plasmid and transfected into cells expressing TetR-NLS, gene expression increased almost 20-fold in growth-arrested cells, and nuclear localization increased by 4-fold.…”
Section: Sequence-specific Nuclear Import Of Plasmid Dnamentioning
confidence: 99%
“…We, and others, have subsequently shown that nuclear import of plasmid DNA is sequence dependent, requires karyopherins (importins) and the small GTPase RAN, and occurs through the nuclear pore complex (NPC). [14][15][16][17][18] In our model of plasmid nuclear import, we propose that transcription factors present in the cytoplasm bind to the DTS and coat the plasmid with nuclear localization sequences (NLSs) that utilize importins to cross the NPC, which regulates the nucleocytoplasmic shuttling of macromolecules during interphase. [19][20][21] We have also developed a tissue-specific DTS, utilizing the smooth muscle g-actin (SMGA) promoter, that mediates nuclear import of pDNA specifically in smooth muscle cells (SMCs).…”
Section: Introductionmentioning
confidence: 99%
“…The high affinity of TetR for the short tetracycline operator DNA sequence, tetO, is used to bind the NLS to the DNA [4]. To improve the TetR system, we have now constructed a TetR fusion protein displaying the HIV-1 TAT peptide (TetR-TAT).…”
Section: Introductionmentioning
confidence: 99%